The effect of hydration learning on concentration through a hydration protocol approach - Andus Suhendro; Bafirman Bafirman; Gusril Gusril; Muhamad Sazeli Rifki (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
The problem in this research was motivated by the low awareness of PSFC futsal athletes about the importance of maintaining fluid balance in the body so that the body is always euhydrated (good) and avoids the risk of dehydration which results in impaired concentration due to lack of fluids. This study aims to determine the effect of hydration status on concentration using a hydration protocol approach in PSFC futsal athletes in the city of Bengkalis. This type of research is an experiment with a pre-experimental research design. One group pre-test post-test research design. The instrument used to measure concentration is the Grid Concentration Test. The total population is 30 people. The sample in the study was 15 futsal athletes at general level. The sampling technique uses purposive sampling technique. Data analysis using Microsoft Excel. The results of research and analysis carried out by researchers show that the hydration protocol directly affects concentration, with a sig value of 0.000 < 0.05. With the concentration test results from 33% the euhydration status was moderate to 73% with an average of very good results.